Applied behavioral and decision sciences in support of US FDA’s drug regulatory mission - Sara L. Eggers; Tamar Krishnamurti; Baruch Fischhoff (Proceedings of the National Academy of Sciences, 2026)
The US Food and Drug Administration (FDA) makes and communicates decisions that directly affect the health choices and well-being of the US public. Behavioral and decision scientists have long supported FDA’s pharmaceutical (medical drug) regulatory and public health mission, working alongside clinical and pharmaceutical scientists. This Perspective describes four interrelated cases illustrating these collaborations: a) creating the Benefit–Risk Framework to guide regulatory decisions regarding new drug approvals; b) launching an internal decision support service to facilitate specific regulatory decisions; c) implementing the Patient-Focused Drug Development initiative to strengthen the use of patient input to inform regulatory decision making; and d) developing FDA SOURCE, a dynamic systems simulation model to assess potential strategies to address the US opioid overdose crisis. Key to the success of these efforts has been their behavioral and decision science foundations, strategically implemented by an expert team dedicated to fostering trusted collaborations with internal and external partners. These cases offer a model for other agencies facing complex decisions of public impact.